2001
DOI: 10.1073/pnas.191003598
|View full text |Cite
|
Sign up to set email alerts
|

When genetic distance matters: Measuring genetic differentiation at microsatellite loci in whole-genome scans of recent and incipient mosquito species

Abstract: Genetic distance measurements are an important tool to differentiate field populations of disease vectors such as the mosquito vectors of malaria. Here, we have measured the genetic differentiation between Anopheles arabiensis and Anopheles gambiae, as well as between proposed emerging species of the latter taxon, in whole genome scans by using 23-25 microsatellite loci. In doing so, we have reviewed and evaluated the advantages and disadvantages of standard parameters of genetic distance, F ST, RST, (␦ ) 2 , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
52
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 36 publications
(54 reference statements)
8
52
0
Order By: Relevance
“…In particular, Lanzaro et al (1998) and Besansky et al (1997) reported limited and extensive introgression of nuclear and mitochondrial markers, respectively. Recent studies have supported the hypothesis of past and contemporary introgression between these two species (Wang et al, 2001;Besansky et al, 2003). With regard to the present topic, the most important conclusion was stated in the following manner: ''The proposed acquisition by An.…”
Section: Anophelesmentioning
confidence: 55%
See 1 more Smart Citation
“…In particular, Lanzaro et al (1998) and Besansky et al (1997) reported limited and extensive introgression of nuclear and mitochondrial markers, respectively. Recent studies have supported the hypothesis of past and contemporary introgression between these two species (Wang et al, 2001;Besansky et al, 2003). With regard to the present topic, the most important conclusion was stated in the following manner: ''The proposed acquisition by An.…”
Section: Anophelesmentioning
confidence: 55%
“…The significant reproductive barriers within this species were apparent from the presence of (1) no heterozygotes for the different variants and (2) nearly total linkage disequilibrium for the pairs of internal transcribed spacer and intergenic spacer genotypes defined as S/type I and M/type II (Gentile et al, 2002). By contrast, other regions of the genome demonstrated no such genetic discontinuities (Wang et al, 2001;Gentile et al, 2002). These opposite patterns of introgression versus no introgression of different genomic regions indicate the semipermeability (Key, 1968) of the S and M genomes; some regions recombine at a high frequency, whereas others, like the rDNA cistron, recombine rarely.…”
Section: Anophelesmentioning
confidence: 99%
“…The other loci (including the rDNA) are at the proximal (centromeric) end of the X chromosome Lehmann et al 2003). However, little differentiation has been found at loci elsewhere in the genome (Gentile et al 2001;Mukabayire et al 2001;Wang et al 2001;Turner et al 2005). Debate is ongoing as to whether such generally limited differentiation primarily reflects insufficient time for differentiation to have occurred or ongoing introgression among forms.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the genetic structure of M and S based on microsatellite markers revealed little between-form differentiation outside the centromeric region of the X chromosome and a few regions associated with inversions (13)(14)(15). This overall lack of divergence was attributed to the homogenizing effect of gene flow between the forms (16).…”
mentioning
confidence: 99%